Clinical Practice Guideline to Improve Locomotor Function Following Chronic Stroke, Incomplete Spinal Cord Injury, and Brain Injury. Issue 1 (January 2020) - Hornby, T. George; Reisman, Darcy S.; Ward, Irene G.; Scheets, Patricia L.; Miller, Allison; Haddad, David; Fox, Emily J.; Fritz, Nora E.; Hawkins, Kelly; Henderson, Christopher E.; Hendron, Kathryn L.; Holleran, Carey L.; et al.
Abstract : Background: Individuals with acute-onset central nervous system (CNS) injury, including stroke, motor incomplete spinal cord injury, or traumatic brain injury, often experience lasting locomotor deficits, as quantified by decreases in gait speed and distance walked over a specific duration (timed distance). The goal of the present clinical practice guideline was to delineate the relative efficacy of various interventions to improve walking speed and timed distance in ambulatory individuals greater than 6 months following these specific diagnoses. Methods: A systematic review of the literature published between 1995 and 2016 was performed in 4 databases for randomized controlled clinical trials focused on these specific patient populations, at least 6 months postinjury and with specific outcomes of walking speed and timed distance. For all studies, specific parameters of training interventions including frequency, intensity, time, and type were detailed as possible. Recommendations were determined on the basis of the strength of the evidence and the potential harm, risks, or costs of providing a specific training paradigm, particularly when another intervention may be available and can provide greater benefit. Results: Strong evidence indicates that clinicians should offer walking training at moderate to high intensities or virtual reality–based training to ambulatory individuals greater than 6 months following acute-onset CNS injury to improve walking speed or distance. In contrast, weak evidence suggests that strength training, circuit (ie, combined) training or cycling training at moderate to high intensities, and virtual reality–based balance training may improve walking speed and distance in these patient groups. Finally, strong evidence suggests that body weight–supported treadmill training, robotic-assisted training, or sitting/standing balance training without virtual reality should not be performed to improve walking speed or distance in ambulatory individuals greater than 6 months following acute-onset CNS injury to improve walking speed or distance. Discussion: The collective findings suggest that large amounts of task-specific (ie, locomotor) practice may be critical for improvements in walking function, although only at higher cardiovascular intensities or with augmented feedback to increase patient's engagement. Lower-intensity walking interventions or impairment-based training strategies demonstrated equivocal or limited efficacy. Limitations: As walking speed and distance were primary outcomes, the research participants included in the studies walked without substantial physical assistance. This guideline may not apply to patients with limited ambulatory function, where provision of walking training may require substantial physical assistance. Summary: The guideline suggests that task-specific walking training should be performed to improve walking speed and distance in those with acute-onset CNS injury although only at higher intensities or with augmented feedback. Future studies should clarify the potential utility of specific training parameters that lead to improved walking speed and distance in these populations in both chronic and subacute stages following injury. Disclaimer: These recommendations are intended as a guide for clinicians to optimize rehabilitation outcomes for persons with chronic stroke, incomplete spinal cord injury, and traumatic brain injury to improve walking speed and distance.